Pengaruh Gaya Kepemimpinan Transformasional dan Transaksional terhadap Kinerja Karyawan: Quality of Work Life sebagai Pemoderasi - Cecilia Engko; Adonia A. Batkunde; Nilam Binti Baharudin (Media Bisnis, 2023)
This study aims to test and analyze empirically the influence of transformational and transactional leadership styles on employee performance with quality of work life as a moderating variable. Collecting data in this study using a questionnaire with saturated sample method. The population of this study was conducted at 12 BUMN companies in Ambon City with the unit of analysis used, namely employees of the finance department. The number of samples collected is 70 and processed by 70 respondents or 100%. Methods of data analysis using a moderated regression model (moderated regression analysis). The results of this study indicate that (1) transformational leadership style has a significant positive effect on employee performance, (2) transactional leadership style has a significant positive effect on employee performance, (3) quality of work life strengthens transformational leadership style on employee performance, (4) quality of work life strengthens the transactional leadership style on employee performance.